Surface modified metal powder and its application in MIM metal injection molding
By activating and modifying the 17-4PH metal powder and forming a double-layer clad structure, the problem of the difference in the molecule between the metal powder and the binder in MIM metal injection molding is solved, the density and strength of the injection blank is improved, and the dimensional stability of the material is enhanced.
Patent Information
- Application Number
- CN202411142340.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2044-08-20
AI Technical Summary
During the MIM metal injection molding process, the intermolecular force difference between the metal powder and the binder leads to low density and strength of the injection blank, and high dimensional change rate of the material during high-temperature degreasing.
By activating and modifying the 17-4PH metal powder, a modified metal powder with a polyolefin coating layer is formed, and a mixed polymer composed of paraformaldehyde, polyurethane elastomer, and ethylene-vinyl acetate copolymer is uniformly coated on the outside of the metal powder by solution mixing to form a double-layer clad structure.
The dispersion of metal powder and its interaction with the binder are improved, the density and strength of the injection blank are improved, deformation and cracking of the injection blank during the subsequent treatment process are reduced, and the dimensional stability of the material is improved.
Smart Images

Figure BDA0005001218910000041 
Figure BDA0005001218910000061 
Figure BDA0005001218910000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal injection molding, and in particular to surface-modified metal powder and application thereof in MIM metal injection molding. Background Art
[0002] MIM metal powder injection molding technology is a new type of powder metallurgy technology formed by introducing modern plastic injection molding technology into the field of powder metallurgy. This technology mixes metal powder with a binder, and then uses injection molding to prepare injection molded blanks. After degreasing and sintering, metal products with complex geometric shapes and high precision are prepared. MIM metal powder injection molding technology has been widely used in consumer electronics, automotive parts, medical devices, hardware tools and other fields due to its advantages such as high design freedom, high strength and low cost.
[0003] However, in the actual application of MIM technology, the properties of metal powder have a crucial impact on the quality and performance of the final product, especially the tap density and dispersibility of metal powder, which directly determine its fluidity and filling properties, and thus affect the density, precision and surface quality of the molded parts.
[0004] Prior art, a Chinese invention patent with publication number CN112191839A, discloses a method for surface modification of metal powder by MIM metal injection molding, comprising the following steps: (S1) raw material addition: adding metal powder raw material prepared by ultra-high pressure water gas combined with atomization into a treatment tank; (S2) modification treatment: adding a treatment liquid containing a certain proportion of a surfactant evenly into the treatment tank for modification treatment, while continuously stirring to allow the metal powder to fully contact with the treatment liquid, the modification treatment time is 30-300 minutes, and the content of the surfactant is 0.01%-1.0%; (S3) powder screening: screening metal powder with a particle size of 0-30 μm after surface modification treatment; (S4) dehydration and drying: dehydrating the metal powder and vacuum drying it.
[0005] It mainly obtains nano-scale metal particles through a series of means, and under the action of surfactants, reduces metal powder agglomeration, improves the physical state of the metal powder surface, and improves the dispersion of the powder. However, MIM metal powder injection molding requires the metal powder to be mixed with a binder for injection molding. Affected by the intermolecular forces between metal dispersion and binder, the improvement of the metal powder's own dispersion does not mean that it also has good dispersion when mixed with the binder. During MIM metal powder injection molding, if the binder is simply mixed with the metal powder, the intermolecular forces between the binder and the metal powder will directly affect the density and strength of the injection blank. The low intermolecular forces between the binder and the metal powder will reduce the density and strength of the injection blank, and lead to insufficient bonding strength at the interface between the binder and the powder. During the high-temperature degreasing process, this weak bonding force makes it impossible for the binder to effectively fix the powder particles, resulting in particle rearrangement or shedding, thereby increasing the size change of the material.
[0006] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a surface-modified metal powder and its application in MIM metal injection molding, so as to solve the technical problems in the prior art of MIM metal injection molding process, that is, the poor intermolecular force between the metal powder and the binder leads to low density and strength of the injected blank, and the high dimensional change rate of the material during high-temperature degreasing.
[0008] The object of the present invention can be achieved by the following technical solution: a surface-modified metal powder, wherein the surface-modified metal powder is obtained by processing the following steps:
[0009] S1. Add the modifier and acetone to the reactor and stir until the system is dissolved, add the activated metal powder to the reactor, increase the temperature of the reactor by 50-55°C, keep it warm and stir for 2-3h, and under normal pressure, increase the temperature of the reactor to 120-140°C at a rate of 2°C / min, keep it warm and stir for 30-50min, and naturally cool the reactor to room temperature to obtain modified metal powder;
[0010] The synthetic reaction principle of modified metal powder is:
[0011] The modified metal powder is prepared by dissolving the modifier in acetone and then dispersing the activated metal powder in the acetone solution to promote mixing of the modifier and the activated metal powder. Then, the temperature of the reaction system is increased to uniformly coat the outside of the activated metal powder with the modifier. In addition, the epoxy group on the activated metal powder can undergo ring-opening condensation with the amino group or the carboxyl group on the modifier under high temperature to form a stable polyolefin coating structure.
[0012] S2, adding the mixed polymer and N-methylpyrrolidone into a reactor, raising the temperature of the reactor to 60-70°C, stirring until the paraformaldehyde is dissolved and dispersed, adding the modified metal powder into the reactor, keeping warm and stirring for 40-60 minutes, lowering the temperature of the reactor to room temperature, adding the dispersion liquid dropwise into the reactor, keeping warm and stirring for 30-50 minutes after the addition is complete, and post-treating to obtain a wet metal powder product;
[0013] S3, mixing the wet metal powder and the benzoyl peroxide solution evenly to obtain a metal powder mixture, and then post-treating to obtain surface-modified metal powder.
[0014] The synthetic reaction principle of surface-modified metal powder is:
[0015] The mixed polymer is dissolved in N-methylpyrrolidone to form a stable N-methylpyrrolidone solution, and then the modified metal powder is dispersed in the N-methylpyrrolidone solution to promote uniform mixing of the mixed polymer and the modified metal powder. The N-methylpyrrolidone is then diluted with a dispersion liquid to promote the mixed polymer to precipitate from the N-methylpyrrolidone, and a mixed polymer coating is formed on the outside of the modified powder. The mixed polymer is then mixed with a benzoyl peroxide solution and freeze-dried to promote mixing of benzoyl peroxide and the metal powder, so as to prepare a surface-modified metal powder.
[0016] Furthermore, in step S1, the amount ratio of the modifier, acetone and activated metal powder is 3-5g:100mL:20-30g; in step S2, the amount ratio of the mixed polymer, N-methylpyrrolidone, modified metal powder and dispersion is 3-4g:15mL:7g:45mL, the mixed polymer is composed of paraformaldehyde, polyurethane elastomer and ethylene-vinyl acetate copolymer in a weight ratio of 5:2:1, the dispersion is composed of purified water, Span 80 and Tween 60 in a weight ratio of 150mL:3g:2g, and the latter The treatment includes: after the reaction is completed, filtering, washing the filter cake with purified water for 3-5 times and then drying to obtain a metal powder wet product; in step S3, the amount ratio of the metal powder wet product and the benzoyl peroxide solution is 3g:2mL, and the benzoyl peroxide solution is composed of benzoyl peroxide and anhydrous ethanol in a weight ratio of 1g:100mL. The post-treatment operation includes: transferring the metal powder mixture to a freeze dryer at a temperature of -20°C, freeze-drying to constant weight, crushing in an environment at a temperature of -10°C, and passing through a 60-mesh sieve to obtain a surface-modified metal powder.
[0017] Further, the activated metal powder is processed by the following steps:
[0018] A1. Add metal powder and activation solution into a reactor, stir for 60-80 min at room temperature, and post-treat to obtain pretreated metal powder;
[0019] A2. Add the pretreated metal powder, anhydrous ethanol and KH-560 into the reactor and stir. The temperature of the reactor is raised to 50-60°C. 1 mol / L sodium hydroxide solution is added into the reactor and the reaction is carried out for 2-3 hours. The activated metal powder is obtained by post-treatment.
[0020] The synthetic reaction formula of the activated powder is:
[0021]
[0022] Where: For pre-treating metal powder particles.
[0023] The synthetic reaction principle of activated metal powder is:
[0024] When pre-treating metal powder, anhydrous ethanol is used as a solvent to promote the uniform dispersion of hydrochloric acid, citric acid, epoxy triacetate and oleic acid amide with the metal powder. Hydrochloric acid is a strong inorganic acid, and citric acid is an organic acid that can form a complex with certain inorganic or organic impurities on the metal surface, thereby helping to remove these impurities. The epoxy group in epoxy triacetate can react with the oxygen-containing active group on the surface of the metal powder to form a chemical bond, forming a dense organic film on the surface of the metal powder, thereby improving the dispersibility and stability of the metal powder and providing more reaction sites for it. Oleic acid amide can form a lubricating film on the surface of the metal powder, which not only reduces the friction and agglomeration between the metal powders, but also improves its compatibility with other materials, thereby preparing a purer pre-treated metal powder.
[0025] The siloxane bonds on KH-560 are hydrolyzed under alkaline conditions and react with the active groups on the surface of the pretreated metal powder to form epoxy modification on the outside of the pretreated metal powder, thereby preparing activated metal powder.
[0026] Further, in step A1, the particle size of the metal powder is 35-55nm, the amount ratio of the metal powder to the activation solution is 3g:8-10mL, the activation solution is composed of 0.05-0.1mol / L hydrochloric acid, 2mol / L citric acid solution, anhydrous ethanol, epoxy triacetate POD and oleic acid amide in an amount ratio of 7mL:4mL:30mL:0.3g:0.2g, and the post-treatment includes: after the reaction is completed, suction filtration, washing the filter cake with purified water until neutral and then drying, and transferring the filter cake to a temperature of In a drying oven at 70-80°C, vacuum drying to constant weight to obtain pretreated metal powder; in step A2, the amount ratio of the pretreated metal powder, anhydrous ethanol, KH-560 and 1 mol / L sodium hydroxide solution is 10g:50-60mL:1-2g:15mL, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, filtered, the filter cake is washed with purified water until neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 70-80°C, and vacuum dried to constant weight to obtain activated metal powder.
[0027] Furthermore, the preparation method of the modifier is: acrylic acid, methyl methacrylate, butyl acrylate, oleylamine and toluene are added to a nitrogen-protected reactor and stirred, the temperature of the reactor is increased to 75-85°C, an initiator is added to the reactor, the reaction is kept warm for 4-6 hours, 3-isocyanate propylene is added to the middle of the reactor, the reaction is kept warm for 60-80 minutes, and the modifier is obtained by post-processing.
[0028] The synthetic reaction formula of the modifier is:
[0029]
[0030] The synthetic reaction principle of the modifier is:
[0031] Under the action of the initiator, the double bonds of the olefins on acrylic acid, methyl methacrylate, butyl acrylate and oleylamine are broken, and a free radical polymerization addition reaction occurs to form a modifier having active groups such as carboxyl and amino groups to modify the polyolefin.
[0032] Furthermore, the molar ratio of acrylic acid, methyl methacrylate, butyl acrylate, oleylamine and 3-isocyanate propylene is 3:5:3:2:2, the usage ratio of acrylic acid, toluene and initiator is 1g:10mL:0.03g, the initiator is composed of azobisisobutyronitrile and n-dodecyl mercaptan in a weight ratio of 3:1, and the post-treatment comprises: after the reaction is completed, the reactor is kept warm at 75-85°C, and the solvent is evaporated under reduced pressure to obtain a modifier.
[0033] Furthermore, the preparation method of the polyurethane elastomer is as follows: 2-butene-1,4-diol, polyethylene glycol, hexamethylene diisocyanate and N,N-dimethylformamide are added to a nitrogen-protected reactor and stirred, the temperature of the reactor is increased to 55-65°C, a catalyst is added to the reactor, the reaction is kept warm for 90-120 minutes, a chain extender is added to the reactor, the reaction is kept warm for 40-60 minutes, a capping agent is added to the reactor, the reaction is kept warm for 60-90 minutes, and a polyurethane elastomer is obtained by post-processing.
[0034] The synthetic reaction formula of polyurethane elastomer is:
[0035]
[0036] Where:
[0037] RI
[0038] R2
[0039] The synthetic reaction principle of polyurethane elastomer is:
[0040] Under the action of a catalyst, hydroxyl groups on 2-butene-1,4-diol and polyethylene glycol undergo condensation polymerization with isocyanate groups on hexamethylene diisocyanate to form a polyurethane prepolymer terminated with isocyanate groups. Then, the isocyanate groups on the polyurethane prepolymer undergo condensation polymerization with hydroxyl groups on a chain extender to increase the degree of crosslinking between molecular chains of the polyurethane prepolymer. The hydroxyl groups on glycidol serve as active groups to react with isocyanate groups on the molecules to form epoxy terminations. Unreacted reactants and by-products generated by the reaction are removed by reduced pressure distillation to prepare a multi-crosslinked polyurethane elastomer with epoxy groups as termination agents and a 2-butene-1,4-diol and polyethylene glycol block prepolymer structure.
[0041] Furthermore, the molar ratio of the 2-butene-1,4-diol, polyethylene glycol and hexamethylene diisocyanate is 3:1:6, the polyethylene glycol is polyethylene glycol 600, the amount ratio of the polyethylene glycol, N,N-dimethylformamide, catalyst, chain extender and end-capping agent is 10g:200mL:0.1g:2g:3g, the catalyst is dibutyltin dilaurate, the chain extender is trimethylolethane, and the end-capping agent is propylene oxide, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is increased to 90°C, and the solvent and low-boiling reactants and by-products are evaporated under reduced pressure to obtain a polyurethane elastomer.
[0042] The present invention also proposes the application of surface-modified metal powder in MIM metal injection molding, that is, the surface-modified metal powder is applied to MIM metal injection molding.
[0043] The present invention has the following beneficial effects:
[0044] 1. The surface-modified metal powder of the present invention selects 17-4PH metal powder as a base powder, activates and modifies it to improve its surface activity, and then coats it with a modifier to form a polyolefin coating layer on the outside of the metal powder. Then, a mixed polymer composed of paraformaldehyde, polyurethane elastomer, and ethylene-vinyl acetate copolymer is dissolved by a solution mixing method, and then mixed with the modified metal powder. Then, the solubility of the polymer is used to promote its slow precipitation from the solution, so that the mixed polymer is uniformly coated on the outside of the polyolefin coating layer of the metal powder, forming a surface-modified metal powder with a double coating. On the one hand, the mixed polymer acts as a coating layer to modify the metal powder, and on the other hand, it acts as a binder, so that the binder and the metal powder can form a premixed combination during MIM metal injection molding; the double-layer coating structure improves the dispersibility of the metal powder and the interaction with the binder, so that during the MIM injection molding process, the metal powder can be arranged and combined more closely, which not only improves the density and strength of the injection blank, but also improves the bending modulus of the injection blank through the mechanical properties of the outer layer of the mixed polymer, and by optimizing the composition of the mixed polymer, reduces the deformation and cracking of the injection blank during subsequent processing, thereby improving the dimensional stability of the material.
[0045] 2. The surface-modified metal powder of the present invention is prepared by preparing a multi-crosslinked polyurethane elastomer with epoxy groups as end-capping agents, 2-butene-1,4-diol and polyethylene glycol block prepolymer structure, and then mixing it with ethylene-vinyl acetate copolymer as a reinforcing material and paraformaldehyde, and dissolving it to form a mixed polymer solution; the polyurethane elastomer contains a large number of polar groups such as hydroxyl groups, carbamate groups and epoxy groups, and the molecular structure of the ethylene-vinyl acetate copolymer has polar vinyl acetate monomers. These groups interact with the aldehyde groups in the paraformaldehyde molecules and the polar groups in N-methylpyrrolidone to produce hydrogen bonds and the like, thereby enhancing the compatibility of the paraformaldehyde, Polyurethane elastomer and ethylene-vinyl acetate form a uniform mixture in N-methylpyrrolidone, thereby forming a uniform mixed polymer coating layer outside the polyolefin layer of the metal powder. The polyolefin coating layer on the metal powder can improve the dispersibility, surface activity and compatibility of the metal powder with the mixed polymer. When mixed at high temperature, the polyolefin on the surface of the metal powder is used as a connecting layer to promote the cross-linking and fusion of the metal powders in the mixed polymer layer. The cross-linking degree of the material is improved by intermolecular force and chemical bonding, thereby improving the green strength and bending modulus of the injection body, reducing the volume change rate during the degreasing process of MIM metal injection molding, and improving the quality of MIM metal injection molding.
[0046] 3. The surface-modified metal powder of the present invention is modified by KH-560 on the surface after the metal powder is activated and modified, so as to improve the reaction activity of the metal powder surface, so that the modifier with a polyolefin structure can be coated on the outside of the metal powder in the form of chemical bonding. During MIM metal injection molding, under the action of high temperature, on the one hand, the excess carboxyl groups and amino groups of the molecular chain segments of the modifier coated on the modified metal powder can undergo ring-opening condensation with the epoxy groups on the polyurethane elastomer to form chemical bonds, and on the other hand, under the initiation of benzoyl peroxide, the polyurethane elastomer can be promoted to form a chemical bond. The unsaturated bonds in the metal powder react with the polyolefin segments on the modifier molecules to undergo free radical addition reactions, thereby increasing the degree of crosslinking between the metal powder and the mixed polymer molecules. Paraformaldehyde is selected as the main component of the mixed polymer. Due to the relatively small molecular weight of paraformaldehyde, small molecular gases such as formaldehyde will be produced during the degreasing and decomposition process. These small molecular gases can easily overflow through the porous outer layer of the green body without destroying the stacking structure of the powder particles, thereby maintaining the dimensional stability of the material and reducing the dimensional changes caused by organic polymer residues, thereby improving the overall performance of the injection green body and the metal injection finished product. DETAILED DESCRIPTION
[0047] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] In this application, epoxy triacetate POD is selected from Shenzhen Xinwei Technology (Group) Co., Ltd.;
[0049] Paraformaldehyde was selected from Yunnan Yuntianhua Co., Ltd.;
[0050] The vinyl acetate content in the ethylene-vinyl acetate copolymer is 30-40%, and the molecular weight of the ethylene-vinyl acetate copolymer is 2000.
[0051] Example 1
[0052] This embodiment provides a method for preparing a surface-modified metal powder, comprising the following steps:
[0053] S1. Preparation of activated metal powder
[0054] 0.05 mol / L hydrochloric acid, 2 mol / L citric acid solution, anhydrous ethanol, epoxy triacetate POD and oleic acid amide were mixed in a dosage ratio of 7 mL: 4 mL: 30 mL: 0.3 g: 0.2 g to obtain an activation solution;
[0055] Select 17-4PH metal powder with a particle size of 35-55 nm as the metal powder;
[0056] Weigh: 600 g of metal powder and 1600 mL of activation solution are added to the reactor, stirred at room temperature for 60 min, and after the reaction is completed, the filter cake is filtered, washed with purified water until neutral, and then dried, and the filter cake is transferred to a drying oven at a temperature of 70°C and vacuum dried to constant weight to obtain pretreated metal powder;
[0057] Weigh: 500g of pretreated metal powder, 2500mL of anhydrous ethanol and 50g of KH-560, add them into the reactor and stir, raise the temperature of the reactor to 50°C, add 750mL of 1mol / L sodium hydroxide solution into the reactor, and keep warm for 2h. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 70°C, and vacuum dry it to constant weight to obtain activated metal powder.
[0058] S2. Preparation of modified metal powder
[0059] Azobisisobutyronitrile and n-dodecyl mercaptan are uniformly mixed in a weight ratio of 3:1 to obtain an initiator;
[0060] Weigh: 216.3 g of acrylic acid, 500.5 g of methyl methacrylate, 384.6 g of butyl acrylate, 535 g of oleylamine and 2163 mL of toluene, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 75° C., add 6.5 g of initiator into the reactor, keep the temperature for 4 h, add 166.2 g of 3-isocyanate propylene into the middle of the reactor, keep the temperature for 60 min, after the reaction is completed, keep the reactor at 75° C., evaporate the solvent under reduced pressure to obtain a modifier;
[0061] Weigh: 60g of the modifier and 2000mL of acetone are added to the reactor and stirred until the system is dissolved, 400g of activated metal powder is added to the reactor, the temperature of the reactor is increased by 50°C, and the mixture is kept warm and stirred for 2h. Under normal pressure, the temperature of the reactor is increased to 120°C at a rate of 2°C / min, and the mixture is kept warm and stirred for 30min. The reactor is naturally cooled to room temperature to obtain modified metal powder.
[0062] S3. Preparation of polyurethane elastomer
[0063] Weigh: 264g of 2-butene-1,4-diol, 600600g of polyethylene glycol, 1009.2g of hexamethylene diisocyanate and 12L of N,N-dimethylformamide, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 55°C, add 6g of dibutyltin dilaurate into the reactor, keep the temperature for 90min, add 120g of trimethylolethane into the reactor, keep the temperature for 40min, add 180g of glycidol into the reactor, keep the temperature for 60min, after the reaction is completed, raise the temperature of the reactor to 90°C, evaporate the solvent and low-boiling reactants and by-products under reduced pressure to obtain a polyurethane elastomer.
[0064] S4. Preparation of mixed polymers
[0065] Paraformaldehyde, polyurethane elastomer and ethylene-vinyl acetate copolymer are uniformly mixed in a weight ratio of 5:2:1 to obtain a mixed polymer;
[0066] S5. Preparation of metal powder
[0067] Purified water, Span 80 and Tween 60 were mixed uniformly in a ratio of 150 mL: 3 g: 2 g to obtain a dispersion for later use;
[0068] Weigh: 300 g of mixed polymer and 1500 mL of N-methylpyrrolidone are added to a reactor, the temperature of the reactor is raised to 60°C, and the polyformaldehyde is stirred until it is dissolved and dispersed. 700 g of modified metal powder is added to the reactor, and the mixture is stirred for 40 minutes at a temperature of 100 °C. The temperature of the reactor is lowered to room temperature, and 4500 mL of the dispersion liquid is added dropwise to the reactor. After the addition is completed, the mixture is stirred for 30 minutes at a temperature of 100 °C. After the reaction is completed, the mixture is filtered, and the filter cake is washed 3 times with purified water and then dried to obtain a wet metal powder product.
[0069] Benzoyl peroxide and anhydrous ethanol were mixed uniformly at a weight ratio of 1 g:100 mL to obtain a benzoyl peroxide solution;
[0070] The wet metal powder and the benzoyl peroxide solution were mixed evenly at a dosage ratio of 3 g:2 mL to obtain a metal powder mixture, and the metal powder mixture was transferred to a freeze dryer at a temperature of -20°C, freeze-dried to constant weight, crushed in an environment at a temperature of -10°C, and passed through a 60-mesh sieve to obtain a surface-modified metal powder.
[0071] Example 2
[0072] This embodiment provides a method for preparing a surface-modified metal powder, comprising the following steps:
[0073] S1. Preparation of activated metal powder
[0074] 0.07 mol / L hydrochloric acid, 2 mol / L citric acid solution, anhydrous ethanol, epoxy triacetate POD and oleic acid amide were mixed in a dosage ratio of 7 mL: 4 mL: 30 mL: 0.3 g: 0.2 g to obtain an activation solution;
[0075] Select 17-4PH metal powder with a particle size of 35-55 nm as the metal powder;
[0076] Weigh: 600 g of metal powder and 1800 mL of activation solution are added to the reactor, stirred at room temperature for 70 min, and after the reaction is completed, filtered, the filter cake is washed with purified water until neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 75°C and vacuum dried to constant weight to obtain pretreated metal powder;
[0077] Weigh: 500g of pretreated metal powder, 2750mL of anhydrous ethanol and 75g of KH-560, add into the reactor and stir, raise the temperature of the reactor to 55°C, add 750mL of 1mol / L sodium hydroxide solution into the reactor, keep warm for 2.5h, after the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at a temperature of 75°C, and vacuum dry to constant weight to obtain activated metal powder.
[0078] S2. Preparation of modified metal powder
[0079] Azobisisobutyronitrile and n-dodecyl mercaptan are uniformly mixed in a weight ratio of 3:1 to obtain an initiator;
[0080] Weigh: 216.3 g of acrylic acid, 500.5 g of methyl methacrylate, 384.6 g of butyl acrylate, 535 g of oleylamine and 2163 mL of toluene, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 80° C., add 6.5 g of initiator into the reactor, keep the temperature for 5 h, add 166.2 g of 3-isocyanate propylene into the middle of the reactor, keep the temperature for 70 min, after the reaction is completed, keep the reactor at 80° C., evaporate the solvent under reduced pressure to obtain a modifier;
[0081] Weigh: 80g of the modifier and 2000mL of acetone are added to the reactor and stirred until the system is dissolved. 500g of activated metal powder is added to the reactor. The temperature of the reactor is increased to 53°C, and the mixture is kept warm and stirred for 2.5h. Under normal pressure, the temperature of the reactor is increased to 130°C at a rate of 2°C / min, and the mixture is kept warm and stirred for 40min. The reactor is naturally cooled to room temperature to obtain modified metal powder.
[0082] S3. Preparation of polyurethane elastomer
[0083] Weigh: 264g of 2-butene-1,4-diol, 600600g of polyethylene glycol, 1009.2g of hexamethylene diisocyanate and 12L of N,N-dimethylformamide, add them into a nitrogen-protected reactor and stir, the temperature of the reactor is raised to 60°C, 6g of dibutyltin dilaurate is added to the reactor, and the reaction is kept warm for 105min, 120g of trimethylolethane is added to the reactor, and the reaction is kept warm for 50min, 180g of glycidol is added to the reactor, and the reaction is kept warm for 75min. After the reaction is completed, the temperature of the reactor is raised to 90°C, and the solvent and low-boiling reactants and by-products are evaporated under reduced pressure to obtain a polyurethane elastomer.
[0084] S4. Preparation of mixed polymers
[0085] Paraformaldehyde, polyurethane elastomer and ethylene-vinyl acetate copolymer are uniformly mixed in a weight ratio of 5:2:1 to obtain a mixed polymer;
[0086] S5. Preparation of metal powder
[0087] Purified water, Span 80 and Tween 60 were mixed uniformly in a ratio of 150 mL: 3 g: 2 g to obtain a dispersion for later use;
[0088] Weigh: 350 g of mixed polymer and 1500 mL of N-methylpyrrolidone are added to a reactor, the temperature of the reactor is raised to 65°C, and the polyformaldehyde is stirred until it is dissolved and dispersed. 700 g of modified metal powder is added to the reactor, and the mixture is stirred for 50 minutes at a temperature of 100 °C. The temperature of the reactor is lowered to room temperature, and 4500 mL of the dispersion liquid is added dropwise to the reactor. After the addition is completed, the mixture is stirred for 40 minutes at a temperature of 100 °C. After the reaction is completed, the mixture is filtered, and the filter cake is washed 4 times with purified water and then dried to obtain a wet metal powder product.
[0089] Benzoyl peroxide and anhydrous ethanol were mixed uniformly at a weight ratio of 1 g:100 mL to obtain a benzoyl peroxide solution;
[0090] The wet metal powder and the benzoyl peroxide solution were mixed evenly at a dosage ratio of 3 g:2 mL to obtain a metal powder mixture, and the metal powder mixture was transferred to a freeze dryer at a temperature of -20°C, freeze-dried to constant weight, crushed in an environment at a temperature of -10°C, and passed through a 60-mesh sieve to obtain a surface-modified metal powder.
[0091] Example 3
[0092] This embodiment provides a method for preparing a surface-modified metal powder, comprising the following steps:
[0093] S1. Preparation of activated metal powder
[0094] 0.1 mol / L hydrochloric acid, 2 mol / L citric acid solution, anhydrous ethanol, epoxy triacetate POD and oleic acid amide were mixed in a dosage ratio of 7 mL: 4 mL: 30 mL: 0.3 g: 0.2 g to obtain an activation solution;
[0095] Select 17-4PH metal powder with a particle size of 35-55 nm as the metal powder;
[0096] Weigh: 600 g of metal powder and 2000 mL of activation solution are added to the reactor, stirred at room temperature for 80 min, and after the reaction is completed, filtered, the filter cake is washed with purified water until neutral and then dried, and the filter cake is transferred to a drying oven at a temperature of 80°C and vacuum dried to constant weight to obtain pretreated metal powder;
[0097] Weigh: 500g of pretreated metal powder, 3000mL of anhydrous ethanol and 100g of KH-560, add into the reactor and stir, raise the temperature of the reactor to 60°C, add 750mL of 1mol / L sodium hydroxide solution into the reactor, and keep warm for 3h. After the reaction is completed, lower the temperature of the reactor to room temperature, filter, wash the filter cake with purified water until it is neutral and then dry, transfer the filter cake to a drying oven at 80°C, and vacuum dry to constant weight to obtain activated metal powder.
[0098] S2. Preparation of modified metal powder
[0099] Azobisisobutyronitrile and n-dodecyl mercaptan are uniformly mixed in a weight ratio of 3:1 to obtain an initiator;
[0100] Weigh: 216.3 g of acrylic acid, 500.5 g of methyl methacrylate, 384.6 g of butyl acrylate, 535 g of oleylamine and 2163 mL of toluene, add them into a nitrogen-protected reactor and stir, raise the temperature of the reactor to 85° C., add 6.5 g of initiator into the reactor, keep the temperature for 6 h, add 166.2 g of 3-isocyanate propylene into the middle of the reactor, keep the temperature for 80 min, after the reaction is completed, keep the reactor at 85° C., evaporate the solvent under reduced pressure to obtain a modifier;
[0101] Weigh: 100 g of the modifier and 2000 mL of acetone, add them into the reactor and stir until the system is dissolved, add 600 g of activated metal powder into the reactor, raise the temperature of the reactor to 55°C, keep warm and stir for 3 hours, under normal pressure, raise the temperature of the reactor to 140°C at a rate of 2°C / min, keep warm and stir for 50 minutes, and naturally cool the reactor to room temperature to obtain modified metal powder.
[0102] S3. Preparation of polyurethane elastomer
[0103] Weigh: 264g of 2-butene-1,4-diol, 600600g of polyethylene glycol, 1009.2g of hexamethylene diisocyanate and 12L of N,N-dimethylformamide, add them into a nitrogen-protected reactor and stir, the temperature of the reactor is raised to 65°C, 6g of dibutyltin dilaurate is added to the reactor, and the reaction is kept warm for 120min, 120g of trimethylolethane is added to the reactor, and the reaction is kept warm for 60min, 180g of glycidol is added to the reactor, and the reaction is kept warm for 90min. After the reaction is completed, the temperature of the reactor is raised to 90°C, and the solvent and low-boiling reactants and by-products are evaporated under reduced pressure to obtain a polyurethane elastomer.
[0104] S4. Preparation of mixed polymers
[0105] Paraformaldehyde, polyurethane elastomer and ethylene-vinyl acetate copolymer are uniformly mixed in a weight ratio of 5:2:1 to obtain a mixed polymer;
[0106] S5. Preparation of metal powder
[0107] Purified water, Span 80 and Tween 60 were mixed uniformly in a ratio of 150 mL: 3 g: 2 g to obtain a dispersion for later use;
[0108] Weigh: 400 g of mixed polymer and 1500 mL of N-methylpyrrolidone are added to a reactor, the temperature of the reactor is raised to 70°C, and the paraformaldehyde is stirred until it is dissolved and dispersed, 700 g of modified metal powder is added to the reactor, and the mixture is stirred for 60 minutes at a temperature of 100 °C. The temperature of the reactor is lowered to room temperature, and 4500 mL of the dispersion liquid is added dropwise to the reactor. After the addition is completed, the mixture is stirred for 50 minutes at a temperature of 100 °C. After the reaction is completed, the mixture is filtered, and the filter cake is washed 5 times with purified water and then dried to obtain a wet metal powder product;
[0109] Benzoyl peroxide and anhydrous ethanol were mixed uniformly at a weight ratio of 1 g:100 mL to obtain a benzoyl peroxide solution;
[0110] The wet metal powder and the benzoyl peroxide solution were mixed evenly at a dosage ratio of 3 g:2 mL to obtain a metal powder mixture, and the metal powder mixture was transferred to a freeze dryer at a temperature of -20°C, freeze-dried to constant weight, crushed in an environment at a temperature of -10°C, and passed through a 60-mesh sieve to obtain a surface-modified metal powder.
[0111] Example 4
[0112] This embodiment provides an application of a surface-modified metal powder in MIM metal injection molding. Specifically, MIM metal injection molding includes the following steps:
[0113] Step 1: Add the surface-modified metal powder prepared in Example 1 into a torque rheometer, raise the temperature of the torque rheometer to 170° C., set the speed to 40 r / min, and mix for 30 minutes to obtain a mixture;
[0114] Step 2: Add the mixture into an injection molding machine at a temperature of 180° C., set the injection pressure to 100 MPa, the holding pressure to 100 MPa, the holding time to 10 s, and naturally cool to room temperature to obtain an injection body;
[0115] Step 3: Place the injection blank in a vacuum atmosphere furnace, and heat the atmosphere furnace to 200°C at a heating rate of 5°C / min, then to 400°C at a heating rate of 3°C / min, then to 600°C at a heating rate of 1°C / min, then to 850°C at a heating rate of 0.5°C / min, and then to 1300°C at a heating rate of 2°C / min. Keep warm for 2 hours, and cool naturally to room temperature to obtain a metal injection finished product.
[0116] Example 5
[0117] This embodiment provides an application of a surface-modified metal powder in MIM metal injection molding. Specifically, MIM metal injection molding includes the following steps:
[0118] Step 1: Add the surface-modified metal powder prepared in Example 2 into a torque rheometer, raise the temperature of the torque rheometer to 175° C., set the speed to 45 r / min, and mix for 35 min to obtain a mixture;
[0119] Step 2: Add the mixture into an injection molding machine at a temperature of 190° C., set the injection pressure to 100 MPa, the holding pressure to 100 MPa, the holding time to 10 s, and naturally cool to room temperature to obtain an injection body;
[0120] Step 3: Place the injection molded body in a vacuum atmosphere furnace, and heat the atmosphere furnace to 200°C at a heating rate of 5°C / min, then to 400°C at a heating rate of 3.5°C / min, then to 650°C at a heating rate of 1.5°C / min, then to 900°C at a heating rate of 0.7°C / min, and then to 1350°C at a heating rate of 2.5°C / min. Keep warm for 2 hours, and cool naturally to room temperature to obtain a metal injection finished product.
[0121] Example 6
[0122] This embodiment provides an application of a surface-modified metal powder in MIM metal injection molding. Specifically, MIM metal injection molding includes the following steps:
[0123] Step 1: Add the surface-modified metal powder prepared in Example 3 into a torque rheometer, raise the temperature of the torque rheometer to 180° C., set the speed to 50 r / min, and mix for 40 min to obtain a mixture;
[0124] Step 2: Add the mixture into an injection molding machine at a temperature of 200° C., set the injection pressure to 100 MPa, the holding pressure to 100 MPa, the holding time to 10 s, and naturally cool to room temperature to obtain an injection blank;
[0125] Step 3: Place the injection blank in a vacuum atmosphere furnace, and heat the atmosphere furnace to 200°C at a heating rate of 5°C / min, then to 400°C at a heating rate of 4°C / min, then to 700°C at a heating rate of 2°C / min, then to 950°C at a heating rate of 0.8°C / min, and then to 1400°C at a heating rate of 3°C / min. Keep warm for 2 hours, and cool naturally to room temperature to obtain a metal injection finished product.
[0126] Comparative Example 1
[0127] The difference between this comparative example and Example 6 is that, during the preparation of the surface-modified metal powder used, step S1 is omitted, and the activated metal powder in step S2 is replaced by the metal powder in step S1.
[0128] Comparative Example 2
[0129] The difference between this comparative example and Example 6 is that, when preparing the surface-modified metal powder used, step S2 is omitted, and the modified metal powder in step S5 is replaced by the activated metal powder prepared in step S1.
[0130] Comparative Example 3
[0131] The difference between this comparative example and Example 6 is that, during the preparation of the surface-modified metal powder used, step S3 is omitted, and no polyurethane elastomer is added to the mixed polymer in step S4.
[0132] Comparative Example 4
[0133] The difference between this comparative example and Example 6 is that, when the surface-modified metal powder is prepared, no paraformaldehyde is added in step S4.
[0134] Performance Test:
[0135] The density, strength and bending modulus of the injection blanks prepared in Examples 4-6 and Comparative Examples 1-4 and the dimensional change rate of the metal injection finished products were tested, wherein the density was tested with reference to the standard GB / T 10421-2002 "Determination of density of sintered metal friction materials"; the strength was tested with reference to the standard GB / T 5160-2002 "Determination of strength of metal powder green billets - rectangular pressed billet transverse fracture method" to determine the green billet strength of the sample; the bending modulus was tested using the CMT4104 universal electronic tensile testing machine produced by Shenzhen Xinsansi Co., Ltd. The international standard ISO178:2001 was used for the test, the displacement rate of the tensile testing machine was set to 0.4 mm / min, and the span was fixed to 64 mm; the dimensional change rate was calculated according to the formula The test was carried out, where L1 is the length of the metal injection finished product, and L0 is the length of the injection blank. The specific test results are shown in Table 1 below.
[0136] Table 1-Performance test data of the sample
[0137]
[0138]
[0139] Data Analysis:
[0140] Comparative analysis of the data in Table 1 above shows that the surface-modified metal powder prepared by the present invention is applied to MIM metal injection molding, and the density of the prepared injection blank reaches 5.19 g / cm 3 The green strength reaches 16.5MPa, the bending modulus reaches 2850MPa, and the metal injection finished product prepared by high-temperature degreasing has a low dimensional change rate and good dimensional stability;
[0141] It is explained that the present invention forms a surface-modified metal powder with a double-layer coating by activating and modifying the metal powder and then performing a primary coating, and then performing a secondary coating with a mixed polymer solution on the basis of the primary coating, so that the metal powder can be more closely arranged and combined during the MIM injection molding process, thereby improving the density and strength of the injected blank, and improving the dimensional stability of the final product by optimizing the composition of the mixed polymer.
[0142] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0143] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0144] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A surface-modified metal powder, characterized in that: The surface-modified metal powder is obtained by processing the following steps: S1. Add the modifier and acetone to the reactor and stir until the system is dissolved, add the activated metal powder to the reactor, increase the temperature of the reactor by 50-55°C, keep it warm and stir for 2-3h, and under normal pressure, increase the temperature of the reactor to 120-140°C at a rate of 2°C / min, keep it warm and stir for 30-50min, and naturally cool the reactor to room temperature to obtain modified metal powder; S2, adding a mixed polymer and N-methylpyrrolidone into a reactor, raising the temperature of the reactor to 60-70°C, stirring until the mixed polymer is dissolved and dispersed, adding modified metal powder into the reactor, keeping warm and stirring for 40-60 minutes, lowering the temperature of the reactor to room temperature, dripping the dispersion into the reactor, keeping warm and stirring for 30-50 minutes, and post-treating to obtain a wet metal powder product, wherein the mixed polymer is composed of paraformaldehyde, polyurethane elastomer, and ethylene-vinyl acetate copolymer in a weight ratio of 5:2:1; S3, mixing the wet metal powder and the benzoyl peroxide solution uniformly to obtain a metal powder mixture, and post-treating to obtain a surface-modified metal powder; The activated metal powder is obtained by the following steps: A1. Add metal powder and activation solution into a reactor, stir at room temperature for 60-80 minutes, and post-treat to obtain pretreated metal powder, wherein the metal powder is 17-4PH metal powder with a particle size of 35-55 nm; A2, adding the pretreated metal powder, anhydrous ethanol and KH-560 into the reactor and stirring, raising the temperature of the reactor to 50-60°C, adding 1 mol / L sodium hydroxide solution into the reactor, keeping the temperature for 2-3 hours, and post-treating to obtain activated metal powder; The preparation method of the polyurethane elastomer is as follows: 2-butene-1,4-diol, polyethylene glycol, hexamethylene diisocyanate and N,N-dimethylformamide are added into a nitrogen-protected reactor and stirred, the temperature of the reactor is increased to 55-65°C, a catalyst is added into the reactor, the reaction is carried out by heat preservation for 90-120 minutes, a chain extender is added into the reactor, the reaction is carried out by heat preservation for 40-60 minutes, a capping agent is added into the reactor, the reaction is carried out by heat preservation for 60-90 minutes, and the polyurethane elastomer is obtained by post-processing.
2. The surface-modified metal powder according to claim 1, characterized in that: In step S1, the dosage ratio of the modifier, acetone and activated metal powder is 3-5g:100mL:20-30g; in step S2, the dosage ratio of the mixed polymer, N-methylpyrrolidone, modified metal powder and dispersion is 3-4g:15mL:7g:45mL, and the dispersion is composed of purified water, Span 80 and Tween 60 in a dosage ratio of 150mL:3g:2g; in step S3, the dosage ratio of the wet metal powder and the benzoyl peroxide solution is 3g:2mL, and the benzoyl peroxide solution is composed of benzoyl peroxide and anhydrous ethanol in a weight ratio of 1g:100mL.
3. The surface-modified metal powder according to claim 1, characterized in that: In step A1, the amount ratio of the metal powder to the activation solution is 3g:8-10mL, and the activation solution is composed of 0.05-0.1mol / L hydrochloric acid, 2mol / L citric acid solution, anhydrous ethanol, epoxy triacetate POD and oleic acid amide in a ratio of 7mL:4mL:30mL:0.3g:0.2g; in step A2, the amount ratio of the pretreated metal powder, anhydrous ethanol, KH-560 and 1mol / L sodium hydroxide solution is 10g:50-60mL:1-2g:15mL.
4. The surface-modified metal powder according to claim 1, characterized in that: The preparation method of the modifier is as follows: acrylic acid, methyl methacrylate, butyl acrylate, oleylamine and toluene are added into a nitrogen-protected reactor and stirred, the temperature of the reactor is increased to 75-85°C, an initiator is added into the reactor, the reaction is kept warm for 4-6 hours, 3-isocyanate propylene is added into the middle of the reactor, the reaction is kept warm for 60-80 minutes, and the modifier is obtained by post-processing.
5. The surface-modified metal powder according to claim 4, characterized in that: The molar ratio of acrylic acid, methyl methacrylate, butyl acrylate, oleylamine and 3-isocyanate propylene is 3:5:3:2:2, the usage ratio of acrylic acid, toluene and initiator is 1g:10mL:0.03g, and the initiator is composed of azobisisobutyronitrile and n-dodecyl mercaptan in a weight ratio of 3:
1.
6. The surface-modified metal powder according to claim 1, characterized in that: The molar ratio of the 2-butene-1,4-diol, polyethylene glycol and hexamethylene diisocyanate is 3:1:6, the polyethylene glycol is polyethylene glycol 600, the amount ratio of the polyethylene glycol, N,N-dimethylformamide, catalyst, chain extender and end-capping agent is 10g:200mL:0.1g:2g:3g, the catalyst is dibutyltin dilaurate, the chain extender is trimethylolethane, and the end-capping agent is propylene oxide.
7. Application of surface modified metal powder in MIM metal injection molding, characterized in that: The surface-modified metal powder according to any one of claims 1 to 6 is applied to MIM metal injection molding.
Citation Information
Patent Citations
MIM metal injection molding metal powder surface modification method and metal powder
CN112191839A
Injection molding feed with modified stainless steel powder and cationic binder
CN115464135A
Method for improving black lines of product in MIM injection process
CN117123780A
Cited By
Metal powder surface modification method for metal forming based on MIM (Metal Injection Molding)
CN121732785A